Creative Writing Assignments in a Second Language Course: A Way to Engage Less Motivated Students - Ekaterina Arshavskaya (Park University, 2015)
This article makes a case for using creative writing in a second language course. Creative writing increases students' enthusiasm for writing skills development and supports students' creativity, which is a fundamental aspect of education. In order to engage less motivated students, a series of creative writing assignments was implemented in a second language writing course. This study presents the rationale for the use of creative writing grounded in critical pedagogy and the context of instruction. Data collection focused on the content of students' writing and their attitudes towards creative writing and critical pedagogy. The results show that all the participating students found the assignment both enjoyable and beneficial for the development of their writing ability. However, the students' perceptions of critical pedagogy varied. The author argues for greater employment of creative writing in second language courses in the future.